SOSIALISASI KONSEP RANTAI PASOK DAN LOGISTIK LAST-MILE DALAM PEMASARAN PRODUK BUMDES MELALUI MARKETPLACE DIGITAL - Fole, Asrul; Erniyani; Safitri, Khoerun Nisa; Kulsaputro, Januar (LPPM Universitas Ibnu Sina, 2026)
Village-Owned Enterprises (BUMDes) play a strategic role in driving rural economic development; however, many still face limitations in supply chain management and distribution logistics, particularly in last-mile delivery to end consumers. These challenges restrict market reach and reduce the efficiency of product marketing. This Community Service Program (PKM) aimed to enhance the understanding and capacity of BUMDes Bumi Pacellekang managers in Gowa Regency to apply supply chain and last-mile logistics concepts through the utilization of digital marketplaces. The methods employed included socialization sessions, interactive discussions, distribution flow mapping simulations, and participatory technical assistance. Evaluation was conducted using pre-test and post-test instruments involving 30 participants. The results indicated a significant improvement in participants’ average understanding, increasing from 56.3% in the pre-test to 80.1% in the post-test, with improvements observed across all assessment indicators. Furthermore, 73% of participants were able to systematically map product distribution flows, and 67% began integrating digital marketplaces into their product marketing activities. Participant satisfaction was high, with 88% stating that the program was highly beneficial. These findings demonstrate that the PKM activities were effective in strengthening BUMDes readiness to expand market access and support the sustainability of village-based enterprises.